Дослідження гіпоглікемічної дії експериментального неін’єкційного інсуліну, створеного методом молекулярного мікрокапсулювання - Каліман, В. П. (Clinical Endocrinology and Endocrine Surgery, 2010)
Article deals with experimental data studying and comparing of antihyperglicemic actvity of prototype microcapsulated non-injected insulin using alloxsan-induced diabetes rat model. Perspectives of its application for treatment of insulin dependent diabetes mellitus as spray and tebleted forms are discussed.